Mapping research trends on mathematics learning media for students with special needs: A bibliometric analysis (2010–2025) - Nanang Khuzaini; Nasrulloh, Muhammad Farid; Fariha, Naela Faza; Rumasoreng, Muhammad Irfan (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Background: Inclusive education has increasingly emphasized the importance of developing learning media that cater to the diverse needs of students, including those with special needs. However, the research landscape on mathematics learning media in this context remains fragmented, necessitating a comprehensive overview to identify patterns, gaps, and future directions. Aim: This study aims to map the development and trends in research related to mathematics learning media for students with special needs within the context of inclusive education from 2010 to 2025. Method: The study employed a bibliometric analysis using data obtained from Scopus, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards to ensure transparency and replicability. Data were analyzed with R Studio (Bibliometrix package) for bibliometric description and VOSviewer for visualizing collaboration networks, thematic evolution, and conceptual structures. Result: The findings indicate a significant increase in publications over the past decade, primarily focusing on assistive technology, inclusive education, and learning disabilities. Three major thematic clusters emerged: (1) Assistive Technology and Learning Innovation, (2) Inclusive Education and Rehabilitation, and (3) Children and Academic Achievement. The collaboration network highlighted dominant contributions from the United States, the United Kingdom, and Australia, suggesting that research in this field is still largely driven by developed countries. The strategic diagram analysis identified special needs education and assistive devices as potential emerging themes. Conclusion: The study reveals a research gap in integrating adaptive technologies such as AI, VR, and AR into inclusive mathematics learning, and in examining their relationship with learning outcomes and individual needs. Future research should emphasize multidisciplinary collaboration among educational technology, psychology, and special education to develop adaptive, inclusive, and student-centered learning media.